Limiting the Risk to Combatant Lives: Confluences Between International Humanitarian Law and Buddhism - Wijenayake, Vishakha (Contemporary buddhism, 2021)
This article places international humanitarian law (IHL) side by side with Buddhist narratives as seen through the Jātakas, to investigate how they view the expectation placed on soldiers to risk their lives in battle. To this end, I delve into the notion of reciprocity of risk in battle from an IHL perspective, which I argue is crucial to infusing warfare with restraint. Similarly, Buddhism acknowledges the importance of reciprocity as an ethical principle that leads to non-violence. I demonstrate how IHL tries to ensure that the risk combatants undertake in combat is limited through its rule of surrender. I compare this argument with the Seyyaṃsa or Seyya Jātaka (no. 282), which illustrates the need to cease violence in cases of surrender. The way militaries treat their own combatants is crucial to the meaningful practice of surrender and thereby the limits and restraints of warfare. Buddhism too encourages rulers to value the lives of their soldiers and not to put their lives at unnecessary risk. I conclude that to maximise the combatant’s choice to limit the risk he takes in battle, IHL should pay more attention to the orders that militaries and armed groups issue to their combatants. Buddhism, for its part, can facilitate the constructive use of military orders because it projects positive images of rulers who are reluctant to order their soldiers to take unnecessary risks in war.